2018
DOI: 10.1371/journal.pone.0196971
|View full text |Cite
|
Sign up to set email alerts
|

Survival and nutritional status of children with severe acute malnutrition, six months post-discharge from outpatient treatment in Jigawa state, Nigeria

Abstract: BackgroundThe Outpatient Therapeutic Program (OTP) for treatment brings the management of Severe Acute Malnutrition (SAM) closer to the community. Many lives have been saved through this approach, but little data exists on the outcome of the children after discharge from such programmes. This study was aimed to determine the survival and nutritional status of children at six months after discharge from OTP for SAM.MethodologyThis was a prospective study of children with SAM admitted into 10 OTPs in two local g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
(19 reference statements)
3
14
1
Order By: Relevance
“…This study shows death rate of 6% from the total participants enrolled, which is acceptable by the SPHERE project minimum international standards for managing SAM in NRU/TFU, and better than the recent study findings from University of Gondar [28] and Hawassa University [31] comprehensive specialized hospitals which found mortality rates of 10.8% for each. It is similar with the findings of two studies done in Ethiopia [25,26] and one conducted in Nigeria [40]. But the mortality rate is greater than that of some studies done in Ethiopia [11,13,35], India [37,38], Ghana [20] and Yemen [36].…”
Section: Discussionsupporting
confidence: 87%
“…This study shows death rate of 6% from the total participants enrolled, which is acceptable by the SPHERE project minimum international standards for managing SAM in NRU/TFU, and better than the recent study findings from University of Gondar [28] and Hawassa University [31] comprehensive specialized hospitals which found mortality rates of 10.8% for each. It is similar with the findings of two studies done in Ethiopia [25,26] and one conducted in Nigeria [40]. But the mortality rate is greater than that of some studies done in Ethiopia [11,13,35], India [37,38], Ghana [20] and Yemen [36].…”
Section: Discussionsupporting
confidence: 87%
“…In the same setting, Kerac et al [27] showed that the death hazard ratio 90 days after discharge decreased with each increased anthropometric measurement unit at admission (HR adjusted for age, edema, and HIV status; 0.80 per cm of MUAC and 0.75 per WHZ unit). Evidence of this relationship between severity at admission and mortality after discharge has also been found for other anthropometric indicators of growth and nutritional status, such as weight-for-age, height-for-age, and head circumference [26][27][28].…”
Section: Discussionmentioning
confidence: 76%
“…The study intended to enrol 50 participants, allowing for detection of 10% mortality with a 95% confidence interval of 3-22%. A 10% mortality rate at six months following discharge was predicted based on the 0.8-10.3% mortality range identified in previous studies [3][4][5][6][7][8][9]. The actual sample size was, however, limited by fewer than anticipated children with SAM being admitted during the study period.…”
Section: Sample Size Estimationmentioning
confidence: 99%
“…Studies conducted in Ethiopia, Malawi, Nigeria, Zimbabwe, Zambia, Bangladesh, and India have described mortality rates ranging between 0.8-10.3% from discharge to up to one year after either hospital or community-based management of SAM [3][4][5][6][7][8][9]. Factors associated with death included younger age (<12 months) and greater malnutrition severity at admission [3][4][5][6][7][8][9]. Mortality was highest among children living with HIV [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation